Pengaruh Tingkat Pemahaman Anggota terhadap Pemahaman Koperasi CU Sawiran dalam Memenuhi Kebutuhan - Aurora, Rif’ Aida Mirza; Utami, Anisa Fitria; Nisa, Fauzatul Laily (Peneliti.net, 2024)
This research aims to evaluate the influence of members' level of understanding on their perception of CU Sawiran Cooperative in meeting their understanding. The study employs a descriptive quantitative approach to collect and analyze data. Data were gathered through questionnaires distributed to the members of CU Sawiran Cooperative and were analyzed using descriptive statistical methods. The findings of this research indicate that the level of members' understanding significantly influences their perception of CU Sawiran Cooperative. Factors such as education, experience as a member, and active participation in cooperative activities play a crucial role in shaping members' understanding of the functions and benefits of CU Sawiran Cooperative. The study also identifies several challenges faced by members in comprehending specific aspects of CU Sawiran Cooperative. Therefore, recommendations are provided to the management of CU Sawiran Cooperative to enhance communication approaches and training programs, enabling members to better comprehend the cooperative concept and the benefits they can derive from it.